Mister Exam

# 126(2,5-x)-173(x-2)=81x-334-237(x+3) equation

The teacher will be very surprised to see your correct solution 😉

v

#### Numerical solution:

Do search numerical solution at [, ]

### The solution

You have entered [src]
126*(5/2 - x) - 173*(x - 2) = 81*x - 334 - 237*(x + 3)
$$126 \left(\frac{5}{2} - x\right) - 173 \left(x - 2\right) = - 237 \left(x + 3\right) + \left(81 x - 334\right)$$
Detail solution
Given the linear equation:
126*((5/2)-x)-173*(x-2) = 81*x-334-237*(x+3)

Expand brackets in the left part
126*5/2-x)-173*x+173*2 = 81*x-334-237*(x+3)

Expand brackets in the right part
126*5/2-x)-173*x+173*2 = 81*x-334-237*x-237*3

Looking for similar summands in the left part:
661 - 299*x = 81*x-334-237*x-237*3

Looking for similar summands in the right part:
661 - 299*x = -1045 - 156*x

Move free summands (without x)
from left part to right part, we given:
$$- 299 x = - 156 x - 1706$$
Move the summands with the unknown x
from the right part to the left part:
$$\left(-143\right) x = -1706$$
Divide both parts of the equation by -143
x = -1706 / (-143)

We get the answer: x = 1706/143
The graph
Rapid solution [src]
     1706
x1 = ----
143 
$$x_{1} = \frac{1706}{143}$$
x1 = 1706/143
Sum and product of roots [src]
sum
1706
----
143 
$$\frac{1706}{143}$$
=
1706
----
143 
$$\frac{1706}{143}$$
product
1706
----
143 
$$\frac{1706}{143}$$
=
1706
----
143 
$$\frac{1706}{143}$$
1706/143
x1 = 11.9300699300699
x1 = 11.9300699300699